Environmental Friendly Method for the Iodination of Moderately Active Arenes - Sathiyapriya, R. (Asian Journal of Chemistry, 2010)
An effective and environmental friendly method for the iodination of various moderately active methoxy arenes, phenols and anilines using hydrogen peroxide and acidified sodium periodate in aqueous ethanol medium is reported. The extent of iodination is easily controlled by stoichiometry and excellent yields of mono iodinated products are obtained.